Reshaping women's history : voices of nontraditional women historians - Gallagher, Julie A.; Winslow, Barbara, 1945- (Women, gender, and sexuality in American history., 2018)
"Award-winning women scholars from nontraditional backgrounds have often negotiated an academic track that leads through figurative--and sometimes literal--minefields. Their life stories offer inspiration, but also describe heartrending struggles and daunting obstacles. Reshaping Women's History presents autobiographical essays by eighteen accomplished scholar-activists who persevered through poverty or abuse, medical malpractice or family disownment, civil war or genocide. As they illuminate their own unique circumstances, the authors also address issues all-too-familiar to women in the academy: financial instability, the need for mentors, explaining gaps in resumes caused by outside events, and coping with gendered family demands, biases, and expectations. Eye-opening and candid, Reshaping Women's History shows how adversity, and the triumph over it, enriches scholarship and spurs extraordinary efforts to affect social change. Contributors: Frances L. Buss, Nupur Chaudhuri, Lisa DiCaprio, Julie R. Enszer, Catherine Fosl, Midori Green, La Shonda Mims, Stephanie Moore, Grey Osterud, Barbara Ransby, Linda Reese, Annette Rodriguez, Linda Rupert, Kathleen Sheldon, Donna Sinclair, Rickie Solinger, Pamela Stewart, Waaseyaa'sin Christine Sy, and Ann Marie Wilson."--ProQuest.